Enhanced Nitrous Oxide Production in Denitrifying Dechloromonas aromatica Strain RCB Under Salt or Alkaline Stress Conditions - Han, Heejoo; Song, Bongkeun; Song, Min Joon; Yoon, Sukhwan (Frontiers in Microbiology, 2019)
Salinity and pH have direct and indirect impacts on the growth and metabolic activities of microorganisms. In this study, the effects of salt and alkaline stresses on the kinetic balance between nitrous oxide (N2O) production and consumption in the denitrification pathway of Dechloromonas aromatica strain RCB were examined. N2O accumulated transiently only in insignificant amounts at low salinity (≤0.5% NaCl) and circumneutral pH (7.0 and 7.5). As compared to these control conditions, incubation at 0.7% salinity resulted in substantially longer lag phase and slower growth rate, along with the increase in the amounts of transiently accumulated N2O (15.8±2.8 µmoles N2O-N/vessel). Incubation at pH 8.0 severely inhibited growth and resulted in permanent accumulation of 29.9±1.3 µmoles N2O-N/vessel from reduction of 151±20 µmoles NO3-/vessel. Monitoring of temporal changes in nirS1, nirS2, and nosZ transcription suggested that the nosZ/(nirS1+nirS2) ratios were indicative of whether N2O was produced or consumed at the time points where measurements were taken. The salt and alkaline stresses altered the N2O consumption kinetics of the resting D. aromatica cells with expressed nitrous oxide reductases. The N2O consumption rates of the cells subjected to the salt and alkaline stress conditions were significantly reduced from 0.84±0.007 µmoles min-1 mg protein-1 of the control to 0.27±0.02 µmoles min-1 mg protein-1 and 0.31±0.03 µmoles min-1 mg protein-1, respectively, when the initial dissolved N2O concentration was 0.1 mM. As the rates of N2O production from NO2- reduction was not significantly affected by the stresses (0.45 – 0.55 µmoles min-1 mg protein-1), the N2O consumption rate was lower than the N2O production rate at the stress conditions, but not at the control condition. These results clearly indicate that the altered kinetics of expressed nitrous oxide reductase and the resultant disruption of kinetic balance between N2O production and consumption was another cause of enhanced N2O emission observed under the salt and alkaline stress conditions. These findings suggest that canonical denitrifiers may become a significant N2O source when faced with abrupt environmental changes.